The screening of breast cancer awareness and health behaviors of women age 40 to 69 in Mus, the least developed city in Turkey: A population based, cross-sectional study. - Ozmen, Tolga; Yuce, Salih; Guler, Tekin; Ulun, Canan; Ozaydin, Nilufer; Pruthi, Sandhya; Ozmen, Vahit (Amer Soc Clinical Oncology, 2015)
[Abstract Not Available]
Annual Meeting of the American-Society-of-Clinical-Oncology (ASCO) / Clinical Science Symposium on Predicting and Improving Adverse Outcomes in Older Adults with Cancer -- MAY 29-JUN 02, 2015 -- Chicago, IL